Role of Exogenous and Endogenous Hydrogen Sulfide (H2S) on Functional Traits of Plants Under Heavy Metal Stresses: A Recent Perspective - Arif, Muhammad Saleem; Yasmeen, Tahira; Abbas, Zohaib; Ali, Shafaqat; Rizwan, Muhammad; Aljarba, Nada H.; Alkahtani, Saad; Abdel-Daim, Mohamed M. (Frontiers in Plant Science, 2021)
Improving growth and productivity of plants that are vulnerable to environmental stresses, such as heavy metals, is of significant importance for meeting global food and energy demands. Because heavy metal toxicity not only causes impaired plant growth, it has also posed many concerns related to human well-being, so mitigation of heavy metal pollution is a necessary priority for a cleaner environment and healthier world. Hydrogen sulfide (H2S), a gaseous signaling molecule, is involved in metal related oxidative stress mitigation and increased stress tolerance in plants. It performs multi-functional roles in plant growth regulation while reducing the adverse effects of abiotic stress. Most effective function of H2S in plants is to eliminate metal related oxidative toxicity by regulating several key physio-biochemical processes. Soil pollution by heavy metals presents significance environmental challenge due to the absence of vegetation cover and the resulting depletion of key soil functions. However, the use of stress alleviators, such as H2S, along with suitable crop plants, has considerable potential for an effective management of these contaminated soils. Overall, the present review examines the imperative role of exogenous application of different H2S donors in reducing HMs toxicity, by promoting plant growth, stabilizing their physio-biochemical processes and up-regulating anti-oxidative metabolic activities. In addition, cross talk of different growth regulators with endogenous H2S and their contribution to the mitigation of metal phytotoxicity has also been explored.